Aristotle’s Criticism of the Platonic Forms as Causes in De Generatione et Corruptione II 9. A Reading Based on Philoponus’ Exegesis - Mouzala, Melina G. (Peitho. Examina Antiqua, 2016)
In the De Generatione et Corruptione II 9, Aristotle aims to achieve the confirmation of his theory of the necessity of the efficient cause. In this chapter he sets out his criticism on the one hand of those who wrongly attributed the efficient cause to other kinds of causality and on the other, of those who ignored the efficient cause. More specifically Aristotle divides all preceding theories which attempted to explain generation and corruption into two groups: i) those which offered an explanation by using the formal cause ii) those which provided an explanation by using the material or the instrumental causes. According to Philoponus, when Aristotle reproaches the other philosophers for adducing no proper notion of the efficient cause he alludes to both Anaxagoras and Plato. Regarding Anaxagoras, in our view this cannot be confirmed by internal textual evidence. In terms of Plato, in this chapter we trace an explicit and an implicit criticism of the Platonic Forms as causes. Aristotle’s implicit criticism is that the Forms are not at all active causes. We can understand better the grounds for this criticism if we also consider his relevant arguments in Book Lambda of his Metaphysics. His explicit criticism, articulated in two arguments, is formulated in GC 335b18–24. We examine the different lines of its interpretation in the secondary literature, but primarily we focus on Philoponus’ exegesis, which contributes significantly, not only to the clarification of Aristotle’s thinking, but also to the manifestation of the arguments articulated in defence of the Platonic theory of the Forms. In this paper, through the analysis of Philoponus’ exegesis we set out to prove that Aristotle’s criticism of the Platonic causes can be construed from the perspective of either Aristotelian theory or the Platonic and Neoplatonic influence. Finally, based on Philoponus’ exegesis, we examine Aristotle’s criticism of those who posited matter or instrumental causes as efficient causes.